Hubungan Aktivitas Fisik dan Resiko Hipertensi Pada Usia Produktif di Salatiga - Christy Pasalbessy; Angkit Kinasih; Fiane Defretes (Jurnal Keperawatan Muhammadiyah, 2021)
Hypertension is a non-communicable disease with an increase in systolic blood pressure 140 mmHg and diastolic 90 mmHg. The results of the examination found in 2016 that the highest blood pressure in Salatiga City was 11.03%. Hypertension is not only experienced by the elderly but is also classified as productive age with prevalence in 2018 based on age 25-34 years at 20.1%, age 35-44 years at 31.6%. At productive age, there is a risk of hypertension due to several influencing factors such as an unhealthy lifestyle, lack of physical activity and 70-80% have a family history of hypertension. To identify and analyze the relationship between physical activity and the risk of hypertension in productive age in Salatiga. Methods: This study uses a quantitative method with a correlation method between the dependent and independent variables. Data collection techniques using a questionnaire. The results of the test of the relationship between the two variables, namely the risk of hypertension and physical activity, obtained n = 0.404 with a significance value of p = <0.005. There are 38% of respondents who have high blood pressure measurement results with the prevalence of risk factors showing that 88% have a family history of high blood pressure, 42% do not take routine treatment, 68% are not aware of a history of high blood pressure, 84% do not take precautions, 86 % were not taking regular medication, 82% ate salty foods, 6% were taking other drugs and 28% had smoking behavior. Meanwhile, in physical activity, it is shown that there are 6% in the light activity category, 72% in the moderate activity category, 22% in the heavy activity category. There is no significant relationship between physical activity and the risk of hypertension in productive age in Salatiga.Risk of hypertension, productive age, physical activity